World Catalogue of the family Lonchaeidae (Diptera, Cyclorrhapha, Acalyptratae) - Macgowan, Iain (Zootaxa, 2023)
A catalogue of world species of Lonchaeidae is provided. Ten valid genera and 611 valid species in two subfamilies are listed. For each valid species the list includes author, year of publication, full publication name, page number of original description and, where known, type locality and type depository. All validly named taxa described before 1 January 2023 are included and for species where there are issues relating to taxonomy, distribution, type status or type depositories, 84 supplementary notes are provided. Colour plates are provided showing a representative species of each genus. The world distribution of Lonchaeidae is tabulated by genus, species and biogeographical realm. Details on species that occur in more than one realm and information on online maps that are available for each species is provided. A synopsis of the fauna of each realm is given that includes references to the key literature sources. The use of following nominal genus as valid is necessary due to the previously used nominal genus not meeting ICZN publication standards: Priscoearomyia Morge, 1963a (previously considered a junior synonym of Protearomyia McAlpine, 1962), new status. The following is a new genus authority necessary due to the previously used authority not meeting ICZN publication standards: Neosilba Waddill & Weems: 1978 (for Neosilba McAlpine, 1962). The following four genus names are new synonyms: Dasyops Bezzi, 1891 (= Dasiops Rondani, 1856), Lonchaba Korytkowski & Ojeda 1971(= Lonchaea Fallén, 1820), Protearomyia Hennig, 1967 (= Priscoearomyia Morge, 1963a) and Togocesa Koçak & Kemal, 2010 (= Lonchaea Fallén, 1820). The following five names represent new species authority details necessary due to the previously used names not meeting ICZN publication standards, or previous mistakes or uncertainties: Priscoearomyia cordillerensis (McAlpine, 1983) (for Protearomyia cordillerensis McAlpine, 1962), Priscoearomyia greciana (McAlpine, 1983) (for Protearomyia greciana McAlpine, 1962), Priscoearomyia martinia (McAlpine, 1983) (for Protearomyia martinia McAlpine, 1962). Lonchaea orientalis MacGowan, 2013 (for Lonchaea orientalis MacGowan, 2007). Neosilba certa (Walker, 1853) (for Neosilba certa (Walker, 1850-1856), Neosilba certa (Walker, 1850) and Neosilba certa (Walker, 1852)). The following four species names are new synonyms: Lonchaea angustitarsis Malloch, 1920a (= Lonchaea deutschi Zetterstedt, 1837), Lonchaea avida McAlpine, 1960 (= Lonchaea choreoides Bezzi, 1923), Lonchaea palpata Czerny, 1934 (= Lonchaea peregrina Becker, 1895), Silba malaysia MacGowan, 2007 (= Silba kuantani MacGowan, this work).The following 12 species names are new combinations: Priscoearomyia cordillerensis (McAlpine, 1983; Protearomyia McAlpine, 1962), Priscoearomyia greciana (McAlpine, 1983: Protearomyia McAlpine, 1962), Priscoearomyia hermonensis (MacGowan & Freidberg, 2008: Protearomyia McAlpine, 1962), Priscoearomyia iberica (MacGowan 2014a: Protearomyia McAlpine, 1962), Priscoearomyia jonesi (MacGowan & Reimann, 2021: Protearomyia McAlpine, 1962), Priscoearomyia mallochi (McAlpine, 1983: Protearomyia McAlpine, 1962), Priscoearomyia martinia (McAlpine, 1983: Protearomyia McAlpine, 1962), Priscoearomyia occidentalis (MacGowan 2016: Protearomyia McAlpine, 1962), Priscoearomyia rameli (MacGowan, 2014a: Protearomyia McAlpine, 1962), Priscoearomyia trichopleura (McAlpine, 1983: Protearomyia McAlpine, 1962), Priscoearomyia withersi (MacGowan, 2014a: Protearomyia McAlpine, 1962), Silba malaysia (MacGowan 2005a; Lonchaea Fallen, 1820) The following new replacement name was necessary due to homonymy: Silba kuantani MacGowan (for Silba malaysia MacGowan, 2007), The following three species are removed from the Lonchaeidae: Lonchaea albimanus Walker, 1858, Lonchaea brasiliensis Walker, 1853 and Lonchaea discrepans Walker, 1861. A First Reviser action was taken on Neosilba laura and N. lauraea Strikis, 2011 with N. laura being chosen here as the correct original spelling.